ORGANIZATION AND IMPROVEMENT OF ACCOUNTING FOR CAPITAL INVESTMENTS IN ENTERPRISES (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the importance of organizing accounting for capital investments in enterprises, modern methods of accounting, and directions for its improvement. The study highlights the role of capital investments in ensuring the financial stability of enterprises, identifies shortcomings in accounting systems, and provides recommendations for their optimization. In addition, the article presents both theoretical foundations and practical suggestions, examining the possibilities of modernizing the capital investment accounting system to enhance the efficiency of enterprise management.